Challenges affecting the World Health Organisation’s Contributions to Sustainable Development in Nigeria - Adesina, Oluwakemi (International Journal of Sustainable Development and Planning, 2023)
This article examines the relationship between health and sustainable development through the lens of cooperation between Nigeria and the World Health Organisation (WHO). While the relationship has yielded some benefits, Nigeria has not fully realized the potential of this cooperation due to various challenges. Drawing on the collective and public good theory, this article investigates the gaps in the WHO's efforts to address policy issues, facilitate collaboration, and manage public health goods. It identifies challenges stemming from three thematic areas: the global health environment, internal issues within the WHO, and the Nigerian context. To fully benefit from the relationship, Nigeria needs to improve coordination within the health sector and ensure the sustainability of WHO programmes. The credibility and technical expertise of the WHO remain valuable for Nigeria’s development.